Leishmania-Derived Murine Monocyte Chemoattractant Protein 1 Enhances the Recruitment of a Restrictive Population of CC Chemokine Receptor 2-Positive Macrophages - Conrad, Sean M. (American Society for Microbiology, 2007)
Transgenic Leishmania parasites that encode the murine chemokine monocyte chemoattractant protein 1 (MCP-1) were generated. These parasites transcribed MCP-1 mRNA and secreted MCP-1 protein. Infection of BALB/c, C57BL/6, or MCP-1 knockout (KO) mice with these parasites resulted in minimal lesion development with fewer parasites in the infected foot, lymph node, and spleen compared to wild-type-infected mice. In contrast, transgenic parasites caused substantial lesions with relatively high numbers of parasites in CC chemokine receptor 2 (CCR2) KO mice, indicating that the parasites are viable and healthy and that the lack of lesion development is CCR2 dependent. Prior infection of mice with transgenic parasites offered no protection to subsequent wild-type L. major challenge, suggesting that the transgenic parasites are controlled by an early innate immune response. Consistent with innate immunity, flow cytometry of cells from the ears of mice infected with transgenic parasites revealed an increase in the number of CCR2-positive macrophages by day 7 postinfection. The enumeration of transgenic parasites in ear lesions demonstrated a significant reduction in parasite numbers, which coincided with the increased CCR2-positive macrophage migration. CCR2-positive macrophages isolated from ears of mice infected with transgenic parasites contained virtually no parasites. In vitro studies revealed that optimal parasite killing required the recruitment of CCR2-positive macrophages, followed by stimulation with a combination of both MCP-1 and gamma interferon (IFN-γ). This work suggests that the parasite-derived MCP-1 can recruit a restrictive population of CCR2-positive macrophages into lesions that can be optimally stimulated by MCP-1 and IFN-γ to efficiently kill Leishmania parasites.